GDP per capita and productivity growth (Edition 2017) (OECD Productivity Statistics, 2017)
This dataset includes indicators on labour productivity growth defined in terms of gross domestic product (GDP), hours worked and capital services. Per capita GDP growth can be broken down into a part which is due to growth in labour productivity (GDP per hour worked) and a part which is due to increased labour utilisation (hours worked per capita). Labour productivity is a key driver of economic growth and changes in living standards, measured notably by growth in GDP per capita. Growth in labour productivity indicates a higher level of output for every hour worked. Labour productivity when measured by Unit Labour Costs (ULC) is also a key driver of international competitiveness. Data are presented as annual datapoints from 1970 onwards